DEVELOPMENT OF TEAMWORK MODEL TOWARDS ACADEMIC ADMINISTRATION OF ISLAMIC PRIVATE SCHOOLS IN THE THREE SOUTHERN BORDER PROVINCES - Cheming, Sabeela; Suwanno, Phimpawee; Kao-ian, Jarunee (Journal of Education and Innovation, 2025)
This research was a research and development. The objectives are 1) to study current conditions and needs of developing which development of teamwork model towards academic administration was achieved through in-depth interviews with six administrators and academic heads by purposive selection and collect quantitative data using with 388 administrators and teachers by stratified random sampling, 2) to develop a teamwork model towards academic administration and model's suitability was evaluated by three experts, and 3) to Test the teamwork model with a target group of 24 teachers and the quality of the model was evaluated based on the Stufflebeam concept. The research instruments included a knowledge test, a team work skills assessment, and a satisfaction questionnaire. The statistics used to analyze the data included the mean, standard deviation, including the Priority Needs Index. The research showed that: 1) The reality is that teamwork of personnel lacks understanding of roles and clear planning, and the need for communication is the highest (PNI Modified = 0.258), followed by interaction (PNI Modified = 0.256) and respect (PNI Modified = 0.255). 2) The teamwork model for academic administration consists of 6 components: principles and reasons, objectives, Procedure, scope of work, evaluation guidelines, and conditions for success. 3) The results of using the teamwork model found that teachers had higher knowledge and teamwork skills after using the model than before using it at a statistical significance level of .05. And the results of the quality check on the accuracy have an evaluation that can analyze both quantitative and qualitative data. In addition, the usefulness also covers stakeholders and related persons. In terms of appropriateness, it can develop teamwork skills and the possibility of being able to be put into practice, it was found that overall it was at a high level.